The many classification range of flight situations - Харченко, В.П.; Остроумов, І.В.; Зайцев, Ю.В. (Proceedings of National Aviation University (archive), 2008)
The multivariate classification principle of flight situation range has been represented. Main parameters of classification flight situation by two parameters (horizontal and vertical deviation from flight planed trajectory) has been estimated.